Tramadol Dependency Treatment: A New Approach - Jamshid Ahmadi (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
Background: Tramadol induced disorder is a new problem. Objective: To explain the efficacy of low dose of clonidine, baclofen and ibuprofen (NSAID) in the treatment of severe and chronic tramadol dependency (2000 mg daily). Method: To evaluate the usefulness of non-narcotic drugs in the management of severe tramadol withdrawal symptoms. Results: Clonidine 0.3 mg, baclofen75 mg and ibuprofen 1200 mg per day is very effective in the management of severe tramadol withdrawal symptoms and craving. Discussion: Our findings indicates that low dose of clonidine, baclofen and ibuprofen (NSAID) is beneficial in the treatment of severe tramadol dependency. This is a fascinating result. Conclusion: To our knowledge dramatic effects combination of clonidine, baclofen and ibuprofen in these situations has not been published yet, and this finding is a considerable addition to the literature.